(untitled) (Південний архів (історичні науки), 2021)
The author reveals the essence of the concept of "entrepreneurship" and "culture of entrepreneurship" – in general, and in the context of modernization transformations of the second half of the XIX – early XX century. The article emphasizes that the concepts of "entrepreneurship" and "entrepreneurship culture" are contextual while retaining standard features. Views on the essence of entrepreneurship by Josef Schumpeter, Alfred Chandler (founder of business history), Franco Amateur, etc., are analyzed. The author refers to the works of Max Weber, Werner Sombart, Rolf Ruttinger in the analysis of the concept of "entrepreneurial culture". In the context of the study, the author defines the culture of entrepreneurship as synonymous with a new system of norms and symbols, forms, methods of entrepreneurial activity, even a new goal (the new author understands as modern, industrial, as opposed to traditional). Entrepreneurship culture is object-subjective and cannot be reduced to socio-psychological, value or motivational components. It includes a set of rules and tools for solving external adaptation and internal integration of resources. The conclusions noted the key features of entrepreneurial culture – eclecticism, instability, low level of innovation, confrontational style of relations with workers, short-sightedness and prevalence of motives for self-affirmation, in relations with the authorities – dependence. Even though the culture of entrepreneurship depends on specific historical factors, it is still an umbrella term.